Jean Baudrillard's Hyperreal: Analysis of Theme in Yoasobi's Song "Idol" - Ismatuloh, Muhammad Aghni (Lakon : Jurnal Kajian Sastra dan Budaya, 2023)
Abstract: Jean Baudrillard is one among many prominent thinkers of postmodernism. One among many his notable idea is the Hyperreal In his book Simulacra and Simulation, Baudrillard's proposes the idea of something that transcend beyond the state of fake and reality, the Hyperreal. This concept can be found as a theme in lyrics of a song titled Idol by Yoasobi. This paper try to dissect the lyrics and finding the implication of Baudrillard's concept of Hyperreal within the implicit and explicit meanings of the lyrics. Idol is a certain profession that has gain significant rise in the 21th century. The common perception is that they are selling ‘fake identities' to their audience. Nevertheless, the truth is more complicated than it is as with using Baudrillard's theoretical framework of the Hyperreal, idol has cross the boundary between falsehood and authenticity and become ‘real' in their own sense. Keywords: Baudrillard, Hyperreal, Simulation, Idol, Yoasobi Abstrak: Jean Baudrillard adalah salah satu dari banyak pemikir terkemuka di bidang pascamodernisme. Salah satu gagasan terkenalnya adalah Hyperreal. Dalam bukunya yang berjudul Simulacra and Simulation, Baudrillard mengusulkan konsep akan sesuatu yang melampaui keadaan palsu dan kenyataan, yaitu Hyperreal. Konsep ini dapat ditemukan sebagai tema dalam lirik lagu berjudul Idol oleh Yoasobi. Artikel penelitian ini mencoba menguraikan lirik lagu tersebut dan menemukan implikasi konsep Hyperreal dari Baudrillard dalam makna tersirat dan tersurat dari lirik. Idol adalah profesi tertentu yang mengalami peningkatan signifikan pada abad ke-21. Persepsi umum tentang idol adalah bahwa mereka menjual 'identitas palsu' kepada audiens. Namun, kenyataannya lebih rumit daripada itu, dengan menggunakan kerangka teoritis Hyperreal dari Baudrillard, profesi Idol telah melampaui batasan antara kepalsuan dan keaslian sehingga menjadi 'nyata' dalam arti mereka sendiri. Kata kunci: Baudrillard, Hyperreal, Simulasi, Idol, Yoasobi